Eksistensi Tradisi Bertenun dan Implikasinya Terhadap Masyarakat - Wa Ode Desy Puspita Hani; La Ode Amaluddin; Surdin; Andrias (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2024)
Weaving is one of the high cultural heritages that is proud of the Indonesian nation and reflects national identity and typical Buton woven cloth is no exception. This research aims to describe the existence of weaving traditions and their implications for the Buton community in Sulaa Village, Baubau City. This research uses a qualitative approach with descriptive methods. The data analysis techniques used are data reduction techniques, data display, and drawing conclusions or verification. The results of this research show that the existence of the weaving tradition of the Sulaa people has existed since ancient times as proven by the existence of historical heritage in the form of (Kampua), namely currency made from woven cloth. The existence of the weaving tradition in Sulaa Village from the past until now has had an impact on the economy and education of the community. These implications encourage the community and local government to continue to preserve it.